Question Apply the Property of Negative Integer Exponents to generate an expression equivalent to 5−94−12 with positive exponents only.(1 point) 5−94−12=

1 answer

To rewrite the expression \( 5^{-9}4^{-12} \) with positive exponents only, we can use the property of negative exponents, which states that \( a^{-n} = \frac{1}{a^n} \).

Applying this property to both parts of the expression:

  1. For \( 5^{-9} \): \[ 5^{-9} = \frac{1}{5^9} \]

  2. For \( 4^{-12} \): \[ 4^{-12} = \frac{1}{4^{12}} \]

Now, we can express the entire expression as: \[ 5^{-9}4^{-12} = \frac{1}{5^9} \times \frac{1}{4^{12}} = \frac{1}{5^9 \cdot 4^{12}} \]

Thus, the expression \( 5^{-9}4^{-12} \) with positive exponents only is: \[ \frac{1}{5^9 \cdot 4^{12}} \]